Evaluation of the reactivity of methanol and hydrogen sulfide residues with the Ziegler–Natta catalyst during polypropylene synthesis and Its effects on polymer properties (2023)
The study focused on the evaluation of the influence of inhibitory compounds such as hydrogen sulfide (H2S) and methanol (CH3OH) on the catalytic productivity and properties of the polymers in the polymerization process with the Ziegler–Natta catalyst. The investigation involved experimental measurements, computational calculations using DFT, and analysis of various parameters, such as molecular weight, melt flow index, xylene solubility, and reactivity descriptors. The results revealed a clear correlation between the concentration of H2S and methanol and the parameters evaluated. Increasing the H2S concentrations, on average by 0.5 and 1.0 ppm, resulted in a drastic decrease in the polymer’s molecular weight. A directly proportional relationship was observed between the flow rate and the H2S concentration. In the case of methanol, the change occurred from 60 ppm, causing a sharp decrease in the molecular weight of the polymer, which translates into an increase in the fluidity index and a decrease in solubility in xylene. The presence of these inhibitors also affected the catalytic activity, causing a reduction in the productivity of the Ziegler–Natta catalyst. Computational calculations provided a deeper understanding of the molecular behavior and reactivity of the studied compounds. The computational calculations yielded significantly lower results compared to other studies, with values of −69.0 and −43.9 kcal/mol for the Ti-CH3OH and H2S interactions, respectively. These results indicate remarkable stability in the studied interactions and suggest that both adsorptions are highly favorable.